Pariwisata Halal Perspektif Ekonomi Syariah: Studi Takhrij Hadis - Wahyudin Darmalaksana; Busro Busro (Politeknik Pariwisata NHI Bandung, 2021)
This research is motivated by the tendency of a literal understanding of Islamic texts regarding compliance with halal tourism based on sharia economics. This study aims to analyze the text of the hadith, which is the basis for compliance with halal tourism from a sharia economic perspective. This study uses a qualitative approach through literature study by applying the takhrij hadith method, while the interpretation in the discussion of this study uses content analysis. The results of this study indicate that the hadith text, which is the basis for compliance with halal tourism from a sharia economic perspective, is of hasan quality because it can be applied as an Islamic practice. The discussion results explain that applying the text of hadith requires contextualization so that it does not narrow the concept of universal halal tourism with a sharia label, especially the necessity of sharia economics. This study concludes that Indonesia is a conducive country through moderate understanding that connects Islamic texts between universal values ​​and local values ​​ to ensure that the homeland can become a centre for halal tourism destinations in the world.